PENERAPAN TEKNIK PEMODELAN DALAM PEMBELAJARAN MENULIS CERPEN - Rahmat Rahmat; Andi Puspitasari (Universitas Negeri Makassar, 2023)
Application of Modeling Techniques in Learning to Write Short Stories. This study aims to describe the learning outcomes of students in class XI IPA 4 SMA Negeri 1 Takalar. This type of research is Classroom Action Research. The research was conducted for two cycles. In cycle 1, the results of observations of teacher activity were in the good category, and student learning activities were in the inactive category. They experienced an increase in cycle II, the results of observations of teacher activity were in the very good category and student activity was in the active category. While the results of writing short stories in cycle I, showed that 15 or 44% of students achieved KKM scores, as many as 19 or 56% of students had not reached KKM scores. Student learning outcomes increased in cycle II by 31 or 91% of students who achieved KKM scores. Based on this, it can be concluded that modeling techniques can improve learning outcomes for short stories.